Anti-N-Methyl-D-Aspartate Receptor Encephalitis Associated With Clear Cell Renal Carcinoma: A Case Report - Yang, Jianhua; Li, Bin; Li, Xiaoquan; Lai, Zhaohui (Frontiers in Oncology, 2020)
Background Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a cause of autoimmune encephalitis, and is characterized by epileptic seizures, psychosis, consciousness impairments. It mostly affects young adults with ovarian cancers. We herein reported a case of anti-NMDAR encephalitis associated with clear cell renal carcinoma. Case presentation A 54-year-old male with headache for 1 week and mood and behavioral changes for 3 days was presented. But his clinical presentation and poor response to antiviral treatment did not support a diagnosis of viral encephalitis. Positive anti-NMDAR antibodies in serum and CSF confirmed autoimmune encephalitis. Subsequent evaluation revealed paraneoplastic etiology of a renal mass, and this was then resected and pathologically confirmed as clear cell renal carcinoma. The patient’s symptoms showed improvement after resecting the mass. The patient relapsed 6 months after discharge, and the symptoms completely disappeared after corticosteroids and intravenous immunoglobulin treatment. Conclusion Our findings suggested that NMDAR encephalitis might be associated with renal clear cell carcinoma. When patients present with unexplained seizures, neuropsychiatric disorder or other brain symptoms, clinicians should be careful with paraneoplastic neurological disorders. Early diagnosis and treatment of primary tumors might show improvement.